Noncanonical regulation of the plasma membrane copper transporter CTRL through modulation of membrane mechanical properties - Chatterjee, Subhendu K.; Kar, Sumanta; Nikte, V, Siddhanta; Dash, Tisha; Ghosh, Tanmoy; Paul, Mrittika; Maji, Saptarshi; Sengupta, Durba; Sinha, Bidisha; Gupta, Arnab (Molecular Biology of the Cell, 2026)
We describe a noncanonical, membrane receptor-like regulation of the human copper transporter-1 (CTR1) in response to copper stimuli. CTR1 is the sole high-affinity trimeric plasma-membrane copper-importing channel that self-regulates by undergoing endocytosis to limit copper uptake. We observed that preceding copper-induced endocytosis, CTR1 forms clusters on the plasma membrane, a phenomenon that is typically observed in membrane receptors. We deciphered the mechanism of CTR1 clustering and studied its ramifications on the physical properties of plasma membranes harboring these clusters that could favor endocytosis. Membrane tension and fluctuation are fundamental regulators of pre-and post-endocytic events. Using coarse-grain molecular dynamics (MD)-simulations and coupled interference reflection microscopy-total internal reflection fluorescence microscopy (TIRF) we demonstrated that CTR1 clusters induce positive membrane curvature, an increase in local membrane tension, and a decrease in local membrane fluctuation; alterations that favor the formation of endocytic pits. Clustering is facilitated by copper sequestering methionine-rich extracellular amino-terminus of CTR1. MD-simulations and IRM-TIRF imaging revealed that CTR1 clustering is facilitated by membrane cholesterol, depletion of which delays CTR1 endocytosis. CTR1 clustering promotes clathrin-coated pit formation that engages recruitment of adaptor protein AP-2. To summarize, we report hitherto unknown ``pre-endocytic'' ``receptor-like'' phenomenon of ligand-induced clustering of a metal channel, which in turn regulates self-endocytosis by modulating membrane properties.